PENGARUH POLA MAKAN DAN STRES AKADEMIK TERHADP KEJADIAN GASTRITIS PADA MAHASISWA DI ERA PANDEMI COVID-19 DI UNIVERSITAS YATSI MADANI TAHUN 2022 - Salsabila Ivanka; Yuni Susilowati (Yayasan Nusantara Hasana Berdikari, 2023)
Diet is a very important habit that can affect the state of nutrition. From the daily eating habits of students that can be seen such as often skipping meals or not eating at all, thus making the stomach empty so that it attacks the stomach and it causes gastritis. Research objectives to determine the influence of diet and academic stress on the incidence of gastritis in students in the era of the COVID-19 pandemic at Yatsi Madani University. This research is quantitative research. This study used a cross-sectional approach. The sample was taken by 145 respondents using total sampling. The instruments used are questionnaire sheets as well as multiple linear regression tests. Based on the results of the Multiple Linear Regression test, resulting in a Sig value = 0.046, it can be concluded